Comparison of topiroxostat and allopurinol in Japanese hyperuricemic patients with or without gout: a phase 3, multicentre, randomized, double‐blind, double‐dummy, active‐controlled, parallel‐group study. (24th April 2016) - Hosoya, T.; Ogawa, Y.; Hashimoto, H.; Ohashi, T.; Sakamoto, R.
Summary: What is known and objective: There are no clinical reports that have compared topiroxostat, a selective xanthine oxidase inhibitor, with allopurinol in serum urate‐lowering efficacy. The aim of this study was to compare the efficacy and safety of topiroxostat and allopurinol in Japanese hyperuricemic patients with or without gout. Methods: A phase 3, multicentre, randomized, double‐blind, double‐dummy, active‐controlled, parallel‐group study conducted in Japan. Patients who had inadequate serum urate levels (a gout patient: serum urate level ≥416·4 μ mol/L; an asymptomatic hyperuricemic patient with specific complications (urinary lithiasis, hypertension, hyperlipidemia and/or diabetes): serum urate level ≥475·8 μ mol/L; and an asymptomatic hyperuricemic patient with no specific complications: serum urate level ≥535·3 μ mol/L) were randomized to topiroxostat 120 mg/day or allopurinol 200 mg/day, with an equal allocation ratio, for 16 weeks. To prevent the onset of gouty arthritis by rapid serum urate reduction, these doses were increased in a stepwise manner. The primary efficacy endpoint was the per cent change in serum urate level from baseline to the final visit. Results and discussion: Overall, 206 patients were randomly assigned to topiroxostat and allopurinol. Two hundred and three patients (allopurinol: n = 105, topiroxostat: n = 98) received at least one dose of the study drug and had their serum urate level assessed at least once. The baseline characteristics were comparable between groups. The mean age of patients was 53·0 ± 11·4 years and 99% of patients were male. The primary efficacy endpoint was −34·3 ± 11·1% in the allopurinol group ( n = 105) and −36·3 ± 12·7% in the topiroxostat group ( n = 98). Non‐inferiority of the serum urate‐lowering efficacy of topiroxostat to allopurinol was proved by the predefined non‐inferiority margin (95% confidence interval, −5·3 to 1·3%). The overall incidences of adverse events and adverse drug reactions were similar between both groups. What is new and conclusion: Topiroxostat 120 mg/day provides non‐inferior serum urate reduction compared with allopurinol 200 mg/day and is well tolerated in Japanese hyperuricemic patients with or without gout.